1996
DOI: 10.1021/bi951600r
|View full text |Cite
|
Sign up to set email alerts
|

Monosialogangliosides of Human Myelogenous Leukemia HL60 Cells and Normal Human Leukocytes. 1. Separation of E-Selectin Binding from Nonbinding Gangliosides, and Absence of Sialosyl-Lex Having Tetraosyl to Octaosyl Core

Abstract: Previous studies suggested that sialosyl-Le(x) (SLex) is a ligand expressed in human neutrophils and myelogenous leukemia HL60 cells which binds to E-selectin and possibly P-selectin. However, clear data on structures of carbohydrate epitopes in these cells were lacking. A systematic study was therefore initiated, employing a large quantity of HL60 cells (> or = 1200 mL packed) and human leukocytes (approximately 100 mL packed). Gangliosides were extracted, followed by extensive fractionation and examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 34 publications
6
47
0
Order By: Relevance
“…[35][36][37][38] Residual E-selectin ligand activity after bromelain treatment would, therefore, be indicative of activity contributed by a non-PSGL-1 glycolipid component. [40][41][42][43][44] Bromelain-treated cells were then analyzed for both HECA-452 and PSGL-1 expression by flow cytometry. In addition, to further verify the complete disappearance of HECA-452 and PSGL-1 expression from the cell surface after bromelain treatment, membrane proteins were prepared as previously described by our laboratory [35][36][37] and analyzed for HECA-452 antigen and PSGL-1 polypeptide by Western blotting.…”
Section: Generation Of Human Cutaneous Lymphocyte-associated Antigen mentioning
confidence: 99%
“…[35][36][37][38] Residual E-selectin ligand activity after bromelain treatment would, therefore, be indicative of activity contributed by a non-PSGL-1 glycolipid component. [40][41][42][43][44] Bromelain-treated cells were then analyzed for both HECA-452 and PSGL-1 expression by flow cytometry. In addition, to further verify the complete disappearance of HECA-452 and PSGL-1 expression from the cell surface after bromelain treatment, membrane proteins were prepared as previously described by our laboratory [35][36][37] and analyzed for HECA-452 antigen and PSGL-1 polypeptide by Western blotting.…”
Section: Generation Of Human Cutaneous Lymphocyte-associated Antigen mentioning
confidence: 99%
“…Numerous reports have described the binding of E-selectin transfected cells to immobilized sLe xcarrying glycolipids (35,55,56), and it was also shown that E-selectin-transfected cells can roll on immobilized glycolipids under physiologic flow conditions (34). However, the contribution of cell surface-expressed glycolipids in the context of a cell surface glycocalyx to the binding of cells on immobilized Eselectin has not yet been analyzed.…”
Section: Binding Of Fuc-tiv and Fuc-tvii Transfectants To E-selectin-mentioning
confidence: 99%
“…It is also noteworthy that E-selectin has been reported to bind with relatively high affinity to certain sialylated polyfucosylated N-linked sugar chains derived from neutrophils, completely independent of any attachment to a polypeptide backbone (52). Likewise, sialylated fucosylated glycolipids from leukocytes can be effective ligands for E-selectin when presented at high density in vitro (53)(54)(55). In all of these instances, definitive proof of in vivo function is currently lacking.…”
mentioning
confidence: 99%